2021
DOI: 10.37934/arfmts.87.3.2130
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Thin Liquid Film with Shear and the Influences on Thermal Energy Transfer at Solid–Liquid Interfaces of Simple Liquid Methane in Contact With (110) Surface Structure of Face-Centred Cubic Lattice (FCC)

Abstract: Thermal energy transfer (TET) is the main performance of contact interfaces which has been studied at a molecular level. Several investigations on TET were accomplished, however, the influences of liquid film thickness on TET have not been sufficiently examined. Thus, this paper analyses the influences of liquid film thickness on TET across solid–liquid (S-L) interfaces. Two liquid film thicknesses (Lz) of 30 Å and 60 Å have been evaluated, and two shear directions (x- and y-directions) have been tested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Oktavitasari et al, [11] performed experimental investigation on vertical axis wind turbine and concluded that best performance turbine spacings in aligned configurations are 3D. Saleman et al, [12] studied the influence of liquid film thickness on thermal energy transfer across solid -liquid interfaces and concluded that the thermal energy transfer is affected by the velocity cut -off at the contact interfaces of solid and liquid. Hassan et al, [13] studied the heat transfer of car radiator with using pure water and water with nano fluid as the coolant by numerical methods and had also verified it experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Oktavitasari et al, [11] performed experimental investigation on vertical axis wind turbine and concluded that best performance turbine spacings in aligned configurations are 3D. Saleman et al, [12] studied the influence of liquid film thickness on thermal energy transfer across solid -liquid interfaces and concluded that the thermal energy transfer is affected by the velocity cut -off at the contact interfaces of solid and liquid. Hassan et al, [13] studied the heat transfer of car radiator with using pure water and water with nano fluid as the coolant by numerical methods and had also verified it experimentally.…”
Section: Introductionmentioning
confidence: 99%